Sharia Compliance of Murabahah of Gold ProductsIn Mandiri Sharia Banks - Adhani, Annisa; Nasim, Arim; Juliana, Juliana; Sobana, Dadang Husen (Iqtisad: Journal of Islamic Economic and Civilization, 2025)
This study aims to measure customer perceptions of sharia compliance of gold murabahah financing products at Bank Syariah Mandiri (BSM) Cianjur Branch Office. The background of this study arose from the differences in views of scholars regarding the validity of non-cash gold buying and selling, which is an important consideration in evaluating sharia financial products. This study uses a descriptive quantitative method with descriptive statistical analysis techniques on data obtained from 92 respondents who use gold installment products. The results of the study indicate that in general, BSM gold installment products are in accordance with DSN-MUI Fatwa No. 77/2010, No. 04/2000, and No. 25/2002, and meet the maqasid sharia parameters. The dimensions of the fatwa related to murabahah and maqasid sharia are in the "very good" category, while the dimensions related to the rahn contract still need improvement although they remain in the "good" category. The implications of these findings indicate that the implementation of gold financing products at BSM Cianjur has a high level of sharia compliance, but there needs to be an evaluation of branch policies related to the rahn aspect to achieve perfection in the application of sharia principles.